(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we will study the effect of some epidemic concepts such as immigrants and vaccine on the dynamical behaviour of epidemic models. The existence, uniqueness and boundedness of the solution are investigated. The local stability analyses of the system is carried out .The global dynamics of the system is investigated numerically.